GROUP CLASSIFICATION OF THE EVOLUTION EQUATION OF SECOND USAGES - Ічанська, Наталія Василівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
This thesis is devoted to investigation of symmetry properties of nonlinear evolution equations. The group classification problem is solver for nonlinear evolutionary equations.